Zero Benefit: Estimating the Effect of Zero Tolerance Discipline Polices on Racial Disparities in School Discipline. (January 2014) - Hoffman, Stephen
This study estimates the effect of zero tolerance disciplinary policies on racial disparities in school discipline in an urban district. Capitalizing on a natural experiment, the abrupt expansion of zero tolerance discipline policies in a mid-sized urban school district, the study demonstrates that Black students in the district were disproportionately affected, with an additional 70 Black students per year recommended for expulsion following the policy change. Furthermore, the study uses negative binomial regression discontinuity analysis to explore the effect of expanding zero tolerance on the proportion of days students are suspended. Following the policy change, the already sizeable difference in the proportion of days suspended between Black students and White students increased.